2022
DOI: 10.1021/acs.iecr.2c01512
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Modeling of Micellization and Adsorption of Surfactants and Surfactant-Like Polymers in Solution: Challenges and Opportunities

Abstract: Surfactants and surfactant-like amphiphilic polymers play important roles in many industrial processes (e.g., home and personal care, laundry, paints and coatings, and biopharmaceuticals). In the past two decades, significant progress has been achieved in understanding and modeling crucial surfactant properties (e.g., critical micellization concentration [CMC], cloud points, adsorption, and stabilization of colloidal particles against flocculation), but many challenges still remain. In this review, several pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 157 publications
0
6
0
Order By: Relevance
“…, coarse-grained (CG) MD simulation is mostly used. 55–57 Fig. 1 shows the schematic view of the emulsion system and displays the molecular structures of the emulsion components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, coarse-grained (CG) MD simulation is mostly used. 55–57 Fig. 1 shows the schematic view of the emulsion system and displays the molecular structures of the emulsion components.…”
Section: Methodsmentioning
confidence: 99%
“…For investigating the morphology of emulsion systems, mesoscale modeling, i.e., coarse-grained (CG) MD simulation is mostly used. [55][56][57] Fig. 1 shows the schematic view of the emulsion system and displays the molecular structures of the emulsion components.…”
Section: Simulation Systemmentioning
confidence: 99%
“…In addition, the discussion here is focused only on a small range of applications of thermodynamic and transport properties studies. As the knowledge increases, , ,, so will our ability to apply these ideas to newer applications. In particular, the use of molecular theory and simulation in conjunction with experimental data to investigate and elucidate behavior at the interface of material science and chemical engineering ,,,, as well as human biology and chemical engineering will provide more enthusiasm and challenge as we start to climb up the technology and value chain described in Figure .…”
Section: Some Additional Thoughtsmentioning
confidence: 99%
“…63 Articles by Lira et al, 46 Lira et al, 48 Fouad et al, 64 and Elliott 65 describe recent developments regarding Wertheim association theory. These are followed by articles on multisolvent electrolytes phase equilibrium by Wang et al, 111 Djamali, 67 and Yang et al, 68 physical property models for adsorption and nanopore, 69,70 molecular simulations for bioseparations, 66 mesoscale modeling of micellization and adsorption of surfactants, 71 use of micelle formation for bioseparations, 72 and non-electrolyte product properties. 73…”
Section: Introductionmentioning
confidence: 99%
“…Although parabola-type formulas have been reported in some cases, gemini or cationic surfactants have to be used in these formulas, and the vertex of the parabola is located in the high-temperature region, higher than room temperature. , In the meantime, most of the rheological studies have focused on dilute system solution, and only a few reports have studied the concentrated surfactant solution, which is close to the real applications. It has been reported that, in a concentrated solution, a giant micelle including wormlike micelle will be formed, which is an important hotspot in surfactant studies due to its unique polymer-like behavior. , In dilute surfactant systems, the shape transition of micelles can be studied by static and dynamic light scattering, while it is not feasible in a concentrated solution. Thus, the giant micelle for the latter has been studied by rheology, NMR, SANS, and visually FF-TEM or cryo-TEM. …”
Section: Introductionmentioning
confidence: 99%